Organizational Communication Strategy of Menantea Purwokerto in Handling Customer Complaints Through Digital Media - Ade Tuti Turistiati; Feby Irawan; Yusmedi Nurfaizal (Persatuan Wartawan Indonesia, 2023)
Menantea Purwokerto uses Instagram to promote its products and engage with its followers. Although Menantea Purwokerto has been successful in utilizing digital media to increase its sales potential, it has been noted that since the opening of Menantea Purwokerto on 5 February 2022, there have been customer complaints that can have a negative impact on Menantea Purwokerto. This study aims to analyze and describe how Menantea Purwokerto's organizational communication strategy handles customer complaints via digital media, what obstacles are encountered when implementing organizational communication, and how solutions are devised to overcome the obstacles encountered. This study employs a qualitative descriptive approach, with data collected via observation, interviews, documentation studies, and literature reviews. The research shows two types of complaints made by customers via digital media: Gofood, Grabfood, Shopeefood, and Menantea Customer Service at 0812-8415xxxx. Menantea Purwokerto encountered internal obstacles such as the distance between the owner and employees, obstacles to individual employee behavior, and external obstacles such as difficulties in handling incoming complaints via Gofood, Grabfood, and Shopeefood when implementing organizational communication. The Menantea Purwokerto conducts an organizational communication audit to address complaints and obstacles in the implementation of organizational communication. For handling complaints and obstacles between Menantea and customers, the Menantea Purwokerto employs a top-down internal communication strategy as well as an external communication strategy.